An Overview Of Pharmacology And Clinical Aspects Concerning The Therapy Of Cochleo-vestibular Syndromes By Intratympanic Drug Delivery - Chirteş, Felician; Albu, Silviu (Medicine and Pharmacy Reports, 2014)
Intratympanic drug delivery refers to drug administration in the middle ear, the main advantage being direct diffusion of substances in the inner ear through the round window membrane with subsequent high intralabiryntine drug concentration and very low systemic side effects. The article is a review of literature concerning the inner ear barrier systems, the physiology of inner ear fluids, intralabirinthine pharmacokinetics and the commonest drugs applied in the middle ear for the treatment of cochleo-vestibular syndromes.